Students' Pronunciation Errors in English Silent Letters - Winda Pusfarani; Mukhrizal Mukhrizal; Hilda Puspita (Journal of English Education and Teaching, 2021)
The objective of this research was to find out the types of pronunciation errors are made by the seventh semester  students of English education study program at Bengkulu University in the academic year 2020/2021. This research used a descriptive quantitative method. 94 students as the total population 30 students  were chosen randomly as the samples. The instrument of the research were pronunciation test and interview. The test comprises 52 sentences which contain 13 silent letters i.e. “k, gh, th, g, p, l, t, s, w, n, b, h, d”. Each letter appears 4 times in the test. The results of the research showed that the students made two types of errors namely pre-systematic errors and systematic errors. The pre-systematic errors occurred more frequently than the systematic errors. The highest errors made by the students  were silent letters “g” (e.g. gnaw) and “b” (e.g. doubt) which total numbers of errors of each of them were 93 times (77%). It could be concluded that the students faced high difficulties in pronouncing the silent letters which completely different from Indonesian phonetic system. It was recommended that the English lecturers should pay more attention to students’ pronunciation and find more suitable method or technique of teaching it and students should study harder about the silent letters in English language.